2004
DOI: 10.1666/0094-8373(2004)030<0652:atrode>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the robustness of disparity estimates: the impact of morphometric scheme, temporal scale, and taxonomic level in spatangoid echinoids

Abstract: The quantification of disparity is an important aspect of recent macroevolutionary stud ies, and it is usually motivated by theoretical considerations about the pace of innovation and the filling of morphospace. In practice, varying protocols of data collection and analysis have rendered comparisons among studies difficult. The basic question remains, How sensitive is any given dis parity signal to different aspects of sampling and data analysis? Here we explore this issue in the context of the radiation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 27 publications
6
64
0
Order By: Relevance
“…Most of the correlations in Tables II and III showed only small changes in Spearman's r, and the amounts of variance in explained by the distance from the centroid typically changed by only 1 -2%. This result provides further support for the findings of Ciampaglio et al (2001) and Villier and Eble (2004) that found little change in disparity results with changes in time slice size. The problem of using absolute numerical ages was also addressed through Figures 2 and 3.…”
Section: Caveatssupporting
confidence: 84%
“…Most of the correlations in Tables II and III showed only small changes in Spearman's r, and the amounts of variance in explained by the distance from the centroid typically changed by only 1 -2%. This result provides further support for the findings of Ciampaglio et al (2001) and Villier and Eble (2004) that found little change in disparity results with changes in time slice size. The problem of using absolute numerical ages was also addressed through Figures 2 and 3.…”
Section: Caveatssupporting
confidence: 84%
“…Due to this, estimates calculated for morphospaces defined for different datasets may not be compatible directly. To remove this effect, several corrected estimates of morphospace volume are introduced (Ciampaglio et al, 2001;Villier & Eble 2004;Wills 2001;Zelditch et al, 2004). One of them is a relative volume calculated to exclude effect of traits number and dimension, another is a unite (or specific) volume calculated to exclude effect of number of objects.…”
Section: Basic Notionsmentioning
confidence: 99%
“…The latter might be of special interest, as it allows to reflect also supposed fractal properties of the entire morphospace and its subspaces. The total morphospace volume and partial volumes of its subspaces are currently being analyzed by various dispersion-based or distance-based methods (Eble, 2000;Faleev et al, 2003;Foote, 1996Foote, , 1997Van Valen, 1974;Villier & Eble, 2004;Zelditch et al, 2004). The main (but not principal) difference is that dispersion-based methods imply a priory decomposition of the entire sample dispersion into within-and between-group dispersions, while distancebased methods are free of such precondition, which provides some specific merits (see below).…”
Section: Operationalizationmentioning
confidence: 99%
See 2 more Smart Citations